A Conceptual Framework for Designing Phylogeography and Landscape Genetic Studies. (1st November 2020) - Ali, Tahir
Abstract: Phylogeography and landscape genetics combines molecular genetics with geography, ecology, and evolutionary biology to develop an understanding of patterns in the spatial distributions of biological diversity. The two disciplines bring together advanced molecular and geospatial tools providing a critical insight on issues that are vital to the field of biogeography, including how and where biodiversity arises, how species respond to changing climates, and how and where conservation efforts should be focused. Although two fields can be considered as merely the fusion of classic biogeography with genetics and genomics, yet both differ in their level of spatial, temporal and system scales along with analytical tools utilized. At the same time, the unique combination of different scientific disciplines and methodical approaches pose a challenge to many researchers who wish to conduct a study at the interface of phylogeography and landscape genetics. A synthesis of the phylogeographic literature presented in this review solely based on the examination of studies that deals with Quaternary climatic oscillations and species' range dynamics across the Palearctic. This review provides a comprehensive overview of the conceptual framework and recent methodological advances in two disciplines and highlights main points to be taken into account while designing a study that represents a window to the past and an opportunity to predict the fate of species due to ongoing climatic and landscape change.